Polytetrafluoroethylene (PTFE) hollow fibre membrane fabrication for organic solvent nanofiltration (OSN) - Francis, Verona Nithya (Nanyang Technological University, 2022)
Membrane technology has allowed purification to be done in a cheaper and more energy efficient way. In organic solvent nanofiltration (OSN), material choice is important as the membrane must be able to withstand harsh solvents over a long time. Although polytetrafuoroethylene (PTFE) is known to be an inert material, little research has been done on using it for OSN membranes, due to fabrication challenges. In this study, the author has successfully synthesized PTFE hollow fibre thin film composites for OSN, despite challenges in the surface morphology and substrate hydrophilicity. The resultant membranes showed to have excellent chemical and mechanical stability when tested in harsh aprotic solvents such as dimethylformamide (DMF) and dimethylsulfoxide (DMSO). They showed high DMF permeance of 3.70 lm-2h-1bar-1, and high acid fuchsin dye rejections of >90%. The membranes were also stable at pressures of up to 5 bar, and overtime.